2013
DOI: 10.1136/bmjopen-2013-003443
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the cervical nerve roots in the diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy: a single-institution, retrospective case–control study

Abstract: ObjectiveTo systematically evaluate the usefulness of assessing the cervical nerve roots by MRI for the diagnosis of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP).DesignSingle-institution, retrospective case–control study.SettingA regional referral hospital.ParticipantsWe retrospectively enrolled 15 consecutive patients with CIDP who satisfied the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) typical and definite criteria and underwent cervical MRI. 30 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…However, abnormal plexus MRI was two to three times less frequent in our cohort than what is reported in typical CIDP [6,7,17,21]. This cannot be explained by the large number (64%) of our patients who received immunomodulatory drugs, as this proportion is similar to those reported in previous studies [6,7,22], nor by our high proportion (36%) of multifocal acquired demyelinating sensory and motor neuropathy, as these forms have been shown to predominantly involve peripheral nerves [17,23]. The prospective multicenter design of our study is unique in the evaluation of plexus MRI in CIDP and probably accounts for this low prevalence of abnormal MRI.…”
Section: Discussionsupporting
confidence: 83%
“…However, abnormal plexus MRI was two to three times less frequent in our cohort than what is reported in typical CIDP [6,7,17,21]. This cannot be explained by the large number (64%) of our patients who received immunomodulatory drugs, as this proportion is similar to those reported in previous studies [6,7,22], nor by our high proportion (36%) of multifocal acquired demyelinating sensory and motor neuropathy, as these forms have been shown to predominantly involve peripheral nerves [17,23]. The prospective multicenter design of our study is unique in the evaluation of plexus MRI in CIDP and probably accounts for this low prevalence of abnormal MRI.…”
Section: Discussionsupporting
confidence: 83%
“…Brachial plexus MRI is an accepted technique for the diagnostic work-up of both CIDP and MMN [5][6][7]11,20,[26][27][28], in particular in the case of abnormal NCS that do not fulfill all electrophysiological consensus criteria for demyelination [3,4]. Several HRUS studies have revealed nerve thickening in patients with chronic inflammatory neuropathies [8][9][10][11][12][13]23,[29][30][31] but, as yet, HRUS abnormalities are not included in sets of diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Gadolinium-DTPA was administered in all patients and the T1-weighted spinecho sequence was repeated after contrast [5,17]. MRIs were rated by experienced neuroradiologists (blinded to the diagnosis, NCS and sonographic findings) for the presence of thickened nerve roots or increased T2 signal and contrast enhancement [5,7,[17][18][19][20].…”
Section: Magnetic Resonance Imaging Studiesmentioning
confidence: 99%
“…For more distal segments, such as cords, divisions or terminal branches, as cut‐off values between normal subjects and CIDP patients still have not been reported, the definition of hypertrophy was based on obvious left–right asymmetries and intraneural fascicular heterogeneity. The target thresholds of nerve intensity to characterize hypersignals that have been reported in the literature were used as a guide . Characteristics of abnormalities: symmetrical or asymmetrical; unifocal (segmental demyelination of a nerve root, plexus or nerve trunk), diffuse (diffuse involvement of neural parenchyma) or multifocal forms; other possible abnormalities – nerve atrophy, muscle abnormalities, loss of normal fascicular pattern (loss of fat signal between the fascicles and nerve segments).…”
Section: Methodsmentioning
confidence: 99%